RELIGIOUS LEADERS AS CULTURAL COMMUNICATORS: AN ANALYSIS OF BEGAWE LOCAL WISDOM IN SOCIO-RELIGIOUS COMMUNICATION IN LOMBOK - Suswandi, Suswandi; Sukarta, Sukarta; Rahmawati, Endang; Nasir, Badlihisham Mohd (Jurnal Al-Ijtimaiyyah, 2026)
This study examines the communicative role of religious leaders in mediating the relationship between Islamic values and local cultural practices within the Begawe tradition of the Sasak community in Lombok. Existing scholarship on religious authority and local wisdom has largely overlooked the discursive mechanisms through which socio religious meanings are negotiated in communal ritual contexts therefore, this study aims to address this gap by analysing how religious narratives are constructed and strategically communicated. Employing a qualitative design grounded in critical discourse analysis, data were collected through in depth interviews, participant observation, and document analysis involving five key informants representing religious, customary, and community leadership. The findings reveal that religious leaders function as cultural brokers who articulate adaptive Islamic discourses by integrating scriptural references, symbolic ritual language, and moral exhortations that legitimise tradition while responding to ongoing socio religious transformations. This mediation process fosters social cohesion and reinforces collective identity, yet also reflects contestations shaped by modernisation and differing Islamic orientations, particularly between Aswaja and Salafi groups. Overall, the study contributes to communication studies and the anthropology of religion by conceptualising local religious discourse as a dynamic cultural strategy for negotiating continuity and change in contemporary Muslim societies.